2009
DOI: 10.1177/1359105309104915
|View full text |Cite
|
Sign up to set email alerts
|

Healthy-eater Identity and Self-efficacy Predict Healthy Eating Behavior: A Prospective View

Abstract: Identity and Self-efficacy Theories were used to examine the relationship between healthy-eater identity, self-efficacy for healthy eating and healthy eating. Measures of healthy-eater identity, perception of healthy eating, nutrition knowledge, self-efficacy for both intake of fruits and vegetables and foods of low nutritional value were completed by 101 university students and staff. Two weeks later, participants recalled recent consumption of (a) fruits and vegetables and (b) foods of low nutritional value.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
87
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 37 publications
12
87
1
2
Order By: Relevance
“…Of the three nutrition behaviors (fruit/vegetable consumption, dinner cooking, and restaurant eating) assessed in our study, only fruit/vegetable consumption was associated with self-efficacy and self-regulation. This finding is in concert with previous studies that addressed positive association of self-efficacy and self-regulation with fruit/vegetable eating (Amnesi, 2011;Anderson et al, 2007;Strachan & Brawley, 2009). A previous study, however, SELF-EFFICACY AND SELF-REGULATON found that higher self-efficacy was related to more frequent preparation of home-based meals and less eating outside the home, especially in fast-food restaurants (Morin, Demers, Turcotte, & Mongeau, 2013).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Of the three nutrition behaviors (fruit/vegetable consumption, dinner cooking, and restaurant eating) assessed in our study, only fruit/vegetable consumption was associated with self-efficacy and self-regulation. This finding is in concert with previous studies that addressed positive association of self-efficacy and self-regulation with fruit/vegetable eating (Amnesi, 2011;Anderson et al, 2007;Strachan & Brawley, 2009). A previous study, however, SELF-EFFICACY AND SELF-REGULATON found that higher self-efficacy was related to more frequent preparation of home-based meals and less eating outside the home, especially in fast-food restaurants (Morin, Demers, Turcotte, & Mongeau, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…Literature shows that self-efficacy influences intention to eat fruits and vegetables in adults aged 20 to 65 without major medical problems (Guillaumie, Godin, Manderscheid, Spitz, & Muller, 2012). In addition, self-efficacy was found in previous studies to be a significant predictor of nutrition and physical activity among overweight or obese women (Fisher & Kridli, 2014), of dietary changes in a low-socioeconomic middle-aged rural population (Shannon et al, 1997), and of fruit/vegetable intakes among young adults (Horacek et al, 2002;Strachan & Brawley, 2009). …”
Section: Self-efficacy and Self-regulatonmentioning
confidence: 94%
“…Commitment to healthy eating is further associated with an individual's social identity as a 'healthy eater' (e.g. Strachan & Brawley, 2009) or the internalisation of this behaviour and the values related to it (i.e. intrinsic motivation; Deci & Ryan, 2011).…”
Section: Motivationmentioning
confidence: 99%
“…Indeed, several studies have shown that higher self-efficacy has been associated with higher healthy food intake in various samples (e.g. Fitzgerald, Heary, Kelly, Nixon, & Shevlin, 2013;Strachan & Brawley, 2009), and self-efficacy has been found to be consistently related to fruit and vegetable consumption in two reviews (Guillaumie et al, 2010;Shaikh et al, 2008).…”
Section: Self-efficacymentioning
confidence: 99%
“…High self-efficacy is associated with good adherence, but high self-efficacy is also required to begin to change one's lifestyle. [10][11][12][13] Purpose of the study In Finnish basic health care, new and more advanced health practices are usually introduced and developed through specially designed projects. These projects aim at improving preventative care in order to improve overall health.…”
Section: Introductionmentioning
confidence: 99%